Computer analysis of the behavior of large-span metal domes with different methods of installation - Lebed, E.V. (Stroitelʹnaâ mehanika inženernyh konstrukcij i sooruženij (Online), 2018)
A brief characteristic of the process of forming the frameworks of large-span metal domes during the installation process is given. A general description of the structural solutions of the frameworks of ribbed domes with annular rings and lattice large-span metal domes is presented. Alternative ways of modeling structural connections of the elements of the frameworks are discussed for domes with different types of structural systems. The load-bearing structural schemes during the assembly of frameworks differ from those, adopted for their analysis and design. Due to this fact, initial internal forces appear in the structural elements of frameworks that are called assembly forces. For the research purpose, design computer models of ribbed dome with annular rings and of sectorial lattice metal dome were developed with the span of 48 m and the height 12 m. The lattice is made of steel I-bars with rigid connections at the joints. The investigated dome frameworks are supported along the contour by permanent columns through hinge supports. On the basis of de-sign models, additional models were created for incomplete frameworks to study alternative ways of erection, which differed from each other in the number of temporary supports with hinge connection to the framework and hinge connections of the bar elements at the joint above the temporary support. Each of these models interpreted the intermediate state of the erected dome framework with its characteristic structural scheme. Depending on the number of temporary supports, three installation schemes were considered for the ribbed-ring dome, and four schemes - for the sectoral-lattice dome. Assembly computer models included the following types of temporary supports: central support, central and one row of intermediate supports, central and three rows of intermediate supports, support under each joint of a frame-work. For each assembly model of the dome framework, computer analysis was performed for the action of its self-weight in order to determine their stress-strain state. Stresses in the structural members, obtained as a result of the analysis, were compared with the stresses in the corresponding elements of the design model of the framework under the self-weight. Based on the obtained data, graphs and diagrams were constructed reflecting the level of assembly stresses in the structural elements of the frame in comparison with design values taking into account the type of work (compression or tension). Various groups of elements are considered along the entire height of the dome frames. The conclusion is made that the stresses in the elements of frameworks of the large-span metal domes are unavoidable when they are erected, and the level of these stresses for specific erection methods is significant. The methods of erection and the types of structural elements that can affect the reliability of dome frames are indicated. The necessity of compulsory analysis of frame-works for erection conditions in the design of large-span metal domes was noted.